Graft polymerization of methacrylic and acrylic acids on preirradiated polyethylene fi lm and evaluation of strength characteristics of graft copolymers - Obshitser, Аrtur S.; Bayburdov, Telman А.; Shmakov, Sergei L.; Shvecova, Ekaterina Yuryevna; Zakharevich, Andrey Machailovich (Известия Саратовского университета. Новая серия: Серия Химия. Биология. Экология)
Membranes on the basis of synthetic and modifi ed natural polymeric substrates are widely used in separation and fi ltration processes and as conductive or isolating media. Grafting acrylic monomers onto polymeric substrates is an eff ective method of their production. Polyethylene, a synthetic polymer, has high strength properties, thermal and chemical resistance, which makes it a good substrate for various products. The objective of this work was producing ion exchange grafted fi lms on the basis of preirradiated polyethylene grafted with methacrylic and acrylic acids, and regulation of their properties during synthesis. Methacrylic and acrylic acids have been grafted onto preirradiated polyethylene fi lm (thickness 30±5 μm) in concentrated solutions with a monomer content up to 45 wt.% in the presence of iron (II) ions at temperatures within 90–97 °C. The concentration of the monomers, initiators, additives of modifi ers and the reaction temperature have been varied. The kinetics of grafting polymerization, grafting degree and the degree of swelling in an electrolyte have been studied by a gravimetric method. The infl uence of the nature of grafted monomers, the concentration of components and modifi ers on the above quantities and mechanical properties of the grafted fi lms have been established. Our modifi ed fi lms have been characterized by FTIR spectroscopy, chemical elemental analysis, scanning electron microscopy (the relief and surface morphology), and their mechanical properties have been assessed by the uniaxial tensile method. The study of the resulting ion exchange composites for the purpose of further application in the technology of treating waste and industrial waters from polyvalent metals and as ion conducting media will be carried out in the future.